Agreement analysis between critical power and intensity corresponding to 50% ∆ in cycling exercise - Souza, Kristopher Mendes De; Lucas, Ricardo Dantas De; Salvador, Paulo Cesar Do Nascimento; Helal, Lucas Crescenti Abdalla Saad; Guglielmo, Luiz Guilherme Antonacci; Greco, Camila Coelho; Denadai, Benedito Sérgio (Universidade Federal de Santa Catarina, 2016)
The purpose of this study was to determine the level of agreement between critical power (CP) and intensity corresponding to 50% of the difference (50% ∆) between oxygen uptake (VO2) at lactate threshold (LT) and maximal oxygen uptake (VO2max) in untrained subjects during cycling exercise. Fifteen healthy male subjects (age: 26.0 ± 3.5 years; body weight: 76.6 ± 10.4 kg; height: 178.2 ± 7.6 cm) volunteered to participate in the study. Each subject performed a series of tests to determine LT, VO2LT, CP, VO2CP, 50% ∆, VO250% ∆, and VO2max. The values LT, CP, VO2CP, 50% ∆, VO250% ∆ and VO2max were 109 ± 15 W, 1.84 ± 0.23 L.min-1, 207 ± 17 W, 2.78 ± 0.27 L.min-1, 206 ± 19 W, 2.77 ± 0.29 L.min-1, and 3.71 ± 0.49 L.min-1, respectively. No signficant difference was found between CP and 50% ∆ (t = 0.16; p = 0.87) or between VO2CP and VO250% ∆ (t = 0.12; p = 0.90). However, the bias ± 95% limits of agreement for comparison between CP and 50% ∆ and between VO2CP and VO250% ∆ were 1 ± 27 W (0.3 ± 14.1%) and 0.01 ± 0.24 L.min-1 (0.2 ± 8.9%), respectively. In summary, the mean CP and 50% ∆ values were not significantly different. However, considering the limits of agreement between the two intensities, CP estimated based on 50% ∆ might result in a remarkable error when the absolute variability of individual differences is taken into account.

A proposta deste estudo foi determinar o nível de concordância entre a potência crítica (PC) e a intensidade correspondente a 50% da diferença (50% ∆) entre o consumo de oxigênio (VO2) no limiar de lactato (LL) e o consumo máximo de oxigênio (VO2max) em sujeitos não treinados durante o exercício de ciclismo. Quinze sujeitos saudáveis do sexo masculino (idade: 26,0 ± 3,5 anos; massa corporal: 76,6 ± 10,4 kg; estatura: 178,2 ± 7,6 cm) participaram deste estudo. Cada sujeito realizou uma série de testes para determinar o LL, VO2.LL, PC, VO2.PC, 50% ∆, VO250% ∆ e VO2max. Os valores de LL, VO2LL, PC, VO2PC, 50% ∆, VO250% ∆ e VO2max foram 109 ± 15 W, 1,84 ± 0,23 L.min-1, 207 ± 17 W, 2,78 ± 0,27 L.min-1, 206 ± 19 W, 2,77 ± 0,29 L.min-1 e 3,71 ± 0,49 L.min-1, respectivamente. Nenhuma diferença significavita foi encontrada entre a PC e o 50% ∆ (t = 0.16; p = 0.87) e entre o VO2PC e o VO250% ∆ (t = 0.12; p = 0.90). Entretanto, o bias ± 95% dos limites de concordância para as comparações entre a PC e o 50% ∆ e entre o VO2PC e o VO250% ∆ foram 1 ± 27 W (0,3 ± 14,1%) e 0,01 ± 0,24 L.min-1 (0,2 ± 8,9%), respectivamente. Em resumo, os valores médios de PC e 50% ∆ não foram significativamente diferentes. No entanto, a PC estimada pelo 50% ∆ pode resultas em um erro significativo quando a cariabilidade individual absoluta é considerada.
Análise de concordância entre a potência crítica e a intensidade correspondente ao 50% ∆ no exercício de ciclismo
Keywords: Exercise intensity; Lactate threshold; Maximal oxygen uptake; Consumo máximo de oxigênio; Intensidade de exercício; Limiar de lactato